In search of true humanity : a voice of protest - Ntshebe, Ephraim Lulamile Cootler (Rhodes University, Faculty of Divinity, Department of Divinity, 1981)
My duty and aim in the writing of the thesis was neither based on scholarship nor on the fluttering of the dove coates of theological orthodoxy, but on the interpretation of the austere nature of the life of black people under the Nationalist Party rule of Apartheid. My duty, therefore, is that of an interpreter of the situation. There is nothing academic about apartheid. What is there is the monstrous evil perpetuated through the genius of the Afrikaner-Broederbond and the Afrikaans Churches and to a lesser extent by the liberal white community within the confines of South Africa (Introduction, p. vii)
Keywords: Church and state -- South Africa; Christianity and politics -- South Africa; Apartheid -- Religious aspects; Human rights -- South Africa; Race relations -- South Africa